Tirāviṭa māpāṭiya āciriyarākiya Mātavac Civañāṉa Yōkikaḷ aruḷicceyta Cōmēcar mutumoḻi veṇpā : mūlamum - Civañāṉa Muṉivar, 18th cent (SAMP early 20th-century Indian books project, 1921)
Stories illustrating maxims from Tirukkuṟaḷ, ancient Tamil didactic verse work, by Tiruvaḷḷuvar; includes text, with commentary.